Case Report: Two Distinct Focal Congenital Hyperinsulinism Lesions Resulting From Separate Genetic Events - Rosenfeld, Elizabeth; Mitteer, Lauren; Boodhansingh, Kara; Becker, Susan A.; McKnight, Heather; Boyajian, Linda; Ackermann, Amanda M.; Kalish, Jennifer M.; Bhatti, Tricia R.; States, Lisa J.; Adzick, N. Scott; Lord, Katherine; et al. (Frontiers in Pediatrics, 2021)
Focal hyperinsulinism (HI) comprises nearly 50% of all surgically treated HI cases and is cured if the focal lesion can be completely resected. Pre-operative localization of the lesion is thus critical. Few cases of hyperinsulinism with multiple focal lesions have been reported, and assessment of the molecular mechanisms driving this rare occurrence has been limited. We present two cases of multifocal HI, each resulting from two independent, pancreatic focal lesions. 18Fluoro-dihydroxyphenylalanine positron emission tomography/computed tomography detected both lesions preoperatively in one patient, whereas identification of the second lesion was an incidental finding during surgical exploration in the other. Complete resection of the focal lesions resulted in cure of the HI in both cases. In each patient, genetic testing of the individual focal lesions revealed different regions of loss of heterozygosity for the maternal 11p15 allele, confirming that each lesion arose from independent somatic events in the setting of a paternally inherited germline ABCC8 mutation. These cases highlight the importance of a multidisciplinary and personalized approach to the management of infants with HI.